2016
DOI: 10.1155/2016/8263926
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Expression Decreases with Reactive Oxygen Species Generation in Rat Cortical Neurons during Early Brain Injury Induced by Experimental Subarachnoid Hemorrhage

Abstract: Sirtuin3 (SIRT3) is an important protein deacetylase which predominantly presents in mitochondria and exhibits broad bioactivities including regulating energy metabolism and counteracting inflammatory effect. Since inflammatory cascade was proved to be critical for pathological damage following subarachnoid hemorrhage (SAH), we investigated the overall expression and cell-specific distribution of SIRT3 in the cerebral cortex of Sprague-Dawley rats with experimental SAH induced by internal carotid perforation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…A further in vitro study showed that SIRT3 expression reduced the level of ROS and maintained ATP production, thus protecting PC12 cells against hypoxic damage via the SOD2 (MnSOD) and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) pathways [ 36 ]. The findings of this present study in a mouse model are supported by the findings in a rat model of SAH and EBI where the expression profile of SIRT3 and the cellular distribution of Sirt3 in the cerebral cortex have been characterized, also indicating the neuroprotective role during the early brain injury following SAH [ 14 ]. Genes that when upregulated offer protection from oxidative tissue damage have been proposed as targets for treatment or prevention of tissue damage and the findings from the present study support the possibility that SIRT3 and its anti-oxidative effects may become a potential therapeutic target for the treatment of EBI [ 37 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A further in vitro study showed that SIRT3 expression reduced the level of ROS and maintained ATP production, thus protecting PC12 cells against hypoxic damage via the SOD2 (MnSOD) and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) pathways [ 36 ]. The findings of this present study in a mouse model are supported by the findings in a rat model of SAH and EBI where the expression profile of SIRT3 and the cellular distribution of Sirt3 in the cerebral cortex have been characterized, also indicating the neuroprotective role during the early brain injury following SAH [ 14 ]. Genes that when upregulated offer protection from oxidative tissue damage have been proposed as targets for treatment or prevention of tissue damage and the findings from the present study support the possibility that SIRT3 and its anti-oxidative effects may become a potential therapeutic target for the treatment of EBI [ 37 ].…”
Section: Discussionsupporting
confidence: 85%
“…Melatonin has been reported to protect the brain against tissue damage following SAH [ 12 ]; melatonin has also recently been shown to protect against diabetic cardiomyopathy via Mst1/Sirt3 signaling pathways [ 13 ]. In 2016, Huang et al reported that decreased expression of SIRT3 was associated with ROS generation in rat cortical neurons during EBI following experimental SAH [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study supports an SIRT-3-dependent neuroprotective role of ketones through the activation antioxidant genes, which, in turn, preserve mitochondrial function (183). In another study, Huang et al showed that in response to a subarachnoid hemorrhage (SAH), SIRT3 levels are reduced (64). SIRT3 was detected in both neurons and endothelial cells and by measuring SOD2 levels, an SIRT3 downstream target; the authors reported a time-dependent increase in its expression after the SAH, which they interpreted as an increase in ROS production.…”
Section: Mitochondrial Sirtuinssupporting
confidence: 54%
“…We have documented in an earlier study that MTPα +/− mice display enhanced extramitochondrial FAO with higher reactive oxygen species generation compared with WT mice ( 3 ). Several recent studies have reported attenuated SIRT3 expression in response to enhanced reactive oxygen species generation ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%